The Impact of Energy Prices on Electricity Production in Egypt - Ahmed, Doaa Akl; Ahmed, Amira Akl (International Journal of Energy Economics and Policy, 2019)
The paper examines the impact of energy prices on electricity generation by different fuel sources (i.e., oil, gas, and hydropower) in Egypt by employing the Autoregressive Distributed Lag approach and bounds test. Two models are estimated where the first accounts for oil prices only whereas the second include both gas and oil prices. In the first model, oil prices negatively affect the electricity produced from oil in the short-run with no impact in the long-run. Also, hydropower is complementary for oil in electricity production only in the short-term whereas gas is a substitute for oil in both long and short terms. In the second model, both energy prices influence electricity generation from oil in both short and long runs while gas and hydropower are respectively, substitute and complementary to oil in both long and short-run. Keywords: Energy prices, Electricity generation, Fuel, elasticity of production JEL Classifications: Q400, Q430 DOI: https://doi.org/10.32479/ijeep.7960